ELF/VLF Wave Radiation Experiment by Modulated Ionospheric Heating Based on Multi-Source Observations at EISCAT - Jing Chen; Jutao Yang; Qingliang Li; Yubo Yan; Shuji Hao; Cheng Wang; Jian Wu; Bin Xu; Tong Xu; Haiqin Che; Linglei He (Atmosphere, 2022)
Ground-based high-frequency modulated waves can periodically heat the ionosphere and create “virtual antennas”, which can radiate extremely low frequency (ELF, 0.3–3 kHz) or very low frequency (VLF, 3–30 kHz) waves for long-distance communication. Ionospheric X-mode and O-mode heating experiments using amplitude and beat-wave (BW) modulations were conducted on 21 November 2019. Experimental results were analyzed from multiple perspectives based on data from Dynasonde, a magnetometer, stimulated electromagnetic emissions, an ELF/VLF signal receiver, and ultra-high-frequency radar. The strongest excited ELF/VLF signals in previous BW modulation heating experiments were around 8–12 kHz; however, in this experiment, no signal excited in this frequency range was observed, and the signal with the highest signal/noise ratio was at the frequency of 3517 Hz, which will aid in understanding the best communication frequency under different ionospheric backgrounds. It is well-accepted that the electron temperature changes periodically with the modulation frequency. However, we noted that the electron temperature had insufficient cooling during the O-mode modulated heating process and then increased again, resulting in a continuous electron temperature increase. We found that this was related to the change in ion composition after analyzing ion-line spectra, which will be helpful in studying the effect of modulation heating on the ionosphere background.